Seismic performance assessment of concrete bridges with traffic-induced fatigue damage. (April 2022) - Gao, Ruofan; He, Jingran
Highlights: A new universal analytical method for seismic performance assessment of traffic-damaged concrete bridges is proposed. The deterministic analysis in the method is developed based on the micro-meso stochastic damage constitutive model. The stochastic response characteristics are depicted in accordance with the probability density evolution theory. The results of an engineering example verify the applicability of the proposed method. Abstract: This paper proposes a universal analytical method for the seismic performance assessment of concrete bridges with initial fatigue damage caused by traffic loads. Load modeling is firstly performed, and random models of traffic load and seismic loads are established using stochastic processes. Subsequently, the theoretical approach for deterministic seismic response analysis of concrete bridges with initial traffic-induced fatigue damage is established by a combination of the micro-meso stochastic damage constitutive models and the finite element numerical method. In this manner, the seismic damage and failure mechanism of concrete bridges with initial fatigue damage can be elucidated. Further, considering the randomness of loads, the stochastic seismic analytical framework of concrete bridges damaged by traffic loads is put forward, in accordance with the probability space partition-based random load combination method and the probability density evolution theory. In such a way, the seismic reliability and safety of existing damaged concrete bridges can be well evaluated. Finally, a railway concrete bridge, as a practical engineering application, is investigated to validate the applicability of the proposed method.